La desorganización familiar y su incidencia en el comportamiento agresivo de los niños y niñas del primer grado de educación general básica de las escuelas: “Manuel Carrión Pinzano” y escuela “Francia”, del cantón Quilanga, provincia de Loja. Período lectivo 2013-2014 - Yaguana Jaramillo, Carmen Elizabeth (2014)
The present study refers to: FAMILY DISRUPTION AND ITS IMPACT ON BASIC GENERAL EDUCATION FIRST GRADE CHILDREN AGGRESSIVE BEHAVIOR OF: "MANUEL CARRIÓN PINZANO" SCHOOLS AND "FRANCE” SCHOOL QUILANGA CANTON, LOJA. PROVINCE LECTIVO PERIOD 2013-2014. It has been structured and developed according to the Rules of Effective Graduation at the National University of Loja. The general objective: To analyze the incidence of Family Disruption in the of Basic General Education First Grade Children Aggressive Behavior, "Manuel Carrión Pinzano" and "France" Schools, the Quilanga Canton, Province of Loja, school 2013-2014. The use of methods for the preparation of this research work were: Scientist, Inductive-Deductive, Analytic-Synthetic, Bibliographical and Statistical Model; the techniques used were: survey aimed at Parents of children in the first grade of basic general education, to establish the Family Disorganization of children in schools; "Manuel Carrión Pinzano" and "France" Schools, the Quilanga Canton and implementation of an Observation Guide to determine the aggressive behavior of children. In the implementation of the Parent survey concludes that: A high percentage of parents surveyed state that they are part of unstable homes, these account for 40%; breaking the bonds of marriage covers 30% of the, while 12% say that Family Disorganization in your home is due to the absence of a parent due to death; domestic violence is given by 10%, the same that can be generated by several factors pointing between these emotional, economic and others. 8% report being single mothers. Accordiing to the Observation Guide is concluded that: 80% do not have Aggressive Behaviors, while 12% are in the minority if you have aggressive behaviors like yelling, gesturing, pushing, no answer, pinching, lie, insult, assault order, destroy foreign objects, kicking, reject biting express hostile words, teasing, name calling, drop to the ground, hitting against the wall, making jokes, 8% conditioned to acquire aggressive behaviors the facts of the moment